The Relationship Between Service Time and Motivation of MTBS Officers With Obedience to Filling in the MTBS Form In Kupang City - Yulianti Kristiani Banhae; Natalia Debi Subani; Yustinus Rindu; Yohanes Mau Abanit (GLOBAL HEALTH SCIENCE GROUP, 2022)
The health status of a nation is largely determined by the infant mortality rate. The research objective was to identify the characteristics of the informants including age and education level, to describe the correlation between length of work and motivation with the obedience of MTBS officers filling out the MTBS form based on references in Kupang City. This type of research is quantitative with a cross-sectional research design. Members of this research are all MTBS officers who have attended MTBS standardization training at the Kupang City Community Health Centres with a total of 30 informants. The representative of this research is the entire population. The tools used in collecting data are questionnaires, direct observation formats and documentation studies. The research data were analyzed by using the Spearman correlation test. The results of the univariate analysis are that the majority of informants are aged 25-35 years, the majority of informants' education is D3 Nurse and bivariate analysis found that p-value = 0.800 > 0.05 which means there is no significant correlation between years of service and the obedience of MTBS officers in filling out the MTBS form in City of Kupang, and the correlation coefficient is 0.052 (very weak relationship) while p-value = 0.000 <α 0.05 with a correlation coefficient: 0.768 (very strong relationship) meaning that there is a significant correlation between work motivation and obedience in filling out the MTBS form by MTBS officers at the City Community Health Centres. Kupang. Conclusion: there is no significant correlation between years of service and adherence to the MTBS form filling by MTBS officers at the Kupang City Community Health Centres, there is a significant correlation between work motivation and adherence to the MTBS form filling by MTBS officers at the Kupang City Community Health Centres.